IP-enabled services - Ellig, Jerry (Regulation (Washington. 1977), 2004)
The Federal Communications Commission has asked for public comment on a wide variety of issues related to the regulatory status of Internet Protocol (IP)-Enabled Services. Key issues include whether IP-enabled services should be subject to economic regulation, pay access charges to local telephone companies, or make contributions to federal universal service programs. The FCC is rightly suspicious of the claim that IP-enabled services should be subject to regulation of prices or entry. There is no evidence that those services can or would be monopolized.